Effect of Curing Temperature Histories on the Compressive Strength Development of High-Strength Concrete - Keun-Hyeok Yang; Jae-Sung Mun; Myung-Sug Cho (Advances in Materials Science and Engineering)
This study examined the relative strength-maturity relationship of high-strength concrete (HSC) specifically developed for nuclear facility structures while considering the economic efficiency and durability of the concrete. Two types of mixture proportions with water-to-binder ratios of 0.4 and 0.28 were tested under different temperature histories including (1) isothermal curing conditions of 5°C, 20°C, and 40°C and (2) terraced temperature histories of 20°C for an initial age of individual 1, 3, or 7 days and a constant temperature of 5°C for the subsequent ages. On the basis of the test results, the traditional maturity function of an equivalent age was modified to consider the offset maturity and the insignificance of subsequent curing temperature after an age of 3 days on later strength of concrete. To determine the key parameters in the maturity function, the setting behavior, apparent activation energy, and rate constant of the prepared mixtures were also measured. This study reveals that the compressive strength development of HSC cured at the reference temperature for an early age of 3 days is insignificantly affected by the subsequent curing temperature histories. The proposed maturity approach with the modified equivalent age accurately predicts the strength development of HSC.